# `y = (2x + 7)(x + 4)` Write the quadratic function in standard form.

*print*Print*list*Cite

### 2 Answers

The standard from is `Ax^2 + Bx + C`

Use First Outer Inner Last (FOIL) to remember how to expand the polynomial.

(2x + 7)(x + 4)

`(2x^2 + 15x + 28)` is the quadratic in standard form.

When we multiply`2x+7`

with `x+4`

We get `2x^2+7x+8x+28`

Which in simpler form is `2x^2+15x+28`

When we shift 'y' to the other side the equation looks like

`2x^2+15x+28-y=0`

There is your quadratic equation

Where a=2, b=15,c=(28-y)